QoS Analysis of Multi Priority DCF Algorithm in Wireless Local Area Network - Sharma, Savitri; Sharma, Vishnu; Goyal, Ankur (International Journal of Computer Sciences and Engineering, 2019)
The network is moving towards the wired to wireless. It has created a great challenge in the design and implementation of the networks. The Medium Access Control (MAC) protocol of the IEEE 802.11 standard plays a major role in the management and coordination of shared channel access and data transmission. This research work focuses on developing new efficient model to enhance the DCF that improves the performance of WLANs. The data rate of the node with packet size is considered and new Multi Priority DCF (MP-DCF Algorithm) is proposed. The proposed scheme decreases the delay and increases the throughput.